Effectiveness of Acupuncture Combined with Nursing in Children with Nondialysis Chronic Kidney Disease: A Retrospective Study - Xuemei Liu (Acupuncture & Electro-Therapeutics Research: International Journal of Integrated Medicine, 2026)
Objective To retrospectively evaluate the effectiveness of acupuncture combined with routine nursing care in improving pruritus, anxiety, depression, sleep quality and quality of life in children with nondialysis chronic kidney disease (CKD), and to provide clinical evidence supporting acupuncture as an adjunctive therapy for pruritus caused by CKD. Methods This single-center retrospective study included 113 children with nondialysis CKD who received treatment between January 2023 and December 2025. According to the treatment documented in the medical records, patients were categorized into a routine nursing group ( n = 51) or an acupuncture plus nursing group ( n = 62). Changes in the Visual Analogue Scale (VAS), 5-D Itch Scale, Self-rating Anxiety Scale (SAS), Self-rating Depression Scale (SDS), Pittsburgh Sleep Quality Index (PSQI) and Kidney Disease Quality of Life-Short Form (KDQOL-SF) scores were compared between baseline and the 8-week follow-up. Multivariable linear regression was performed to determine the independent association between acupuncture and improvement in pruritus, while subgroup analyses evaluated the consistency of treatment effects across different primary renal diseases and baseline pruritus severity. Results No statistically significant differences were observed in baseline characteristics between the two groups (all P > 0.05). After treatment, both groups demonstrated significant reductions in VAS and 5-D Itch Scale scores (both P < 0.001). Compared with routine nursing alone, acupuncture combined with nursing resulted in significantly lower 5-D Itch Scale scores (9.74 ± 4.70 vs. 12.76 ± 4.71, P < 0.001) and VAS scores (3.11 ± 1.29 vs. 3.76 ± 1.42, P = 0.012). The acupuncture group also showed significantly lower SAS scores (42.52 ± 7.47 vs. 47.27 ± 8.03, P = 0.001), lower PSQI total scores (7.35 ± 2.40 vs. 9.86 ± 2.54, P < 0.001) and higher KDQOL-SF scores for both the general health and kidney disease-specific domains (both P < 0.001). Multivariable analysis showed that acupuncture was independently associated with greater improvement in pruritus ( β = 3.87, 95% confidence interval: 2.68–5.05, P < 0.001). No statistically significant interactions were detected across subgroups defined by primary renal disease or baseline pruritus severity, although these exploratory analyses were limited by small subgroup sample sizes (all P for interaction > 0.05). Conclusions In children with nondialysis CKD, acupuncture combined with routine nursing care was associated with greater improvement in pruritus, anxiety, sleep quality, and quality of life than routine nursing alone. Acupuncture was independently associated with pruritus improvement, and its relative effectiveness remained consistent across different patient subgroups.